2018
DOI: 10.1111/are.13642
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope analysis to quantify contributions of supplementary feed in Nile Tilapia Oreochromis niloticus (GIFT strain) aquaculture

Abstract: Nile tilapia (Oreochromis niloticus) is currently one of the most farmed freshwater fish and contributes significantly to total global aquaculture production. The genetically improved strain of O. niloticus (GIFT) was introduced to Papua New Guinea (PNG) in 1999 to improve food and income security. The high cost and low availability of commercial fish feed hinder the growth of GIFT farming in PNG. Stable carbon and nitrogen isotopes were used to determine the role of supplementary and natural food sources in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 56 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…Small-scale piggeries and vegetable cropping also occur in the catchment of the farms, and urban activities in the nearby town of Kainantu, may also be sources of nutrients; however, their contribution to the nutrient budgets of the farms is likely to be negligible. Despite the use of chicken manure, a previous study has shown that this type of organic fertiliser does not influence the growth and δ 15 N of GIFT [11]. This indicates that the enrichment of δ 15 N in vegetable-fed GIFT in our study is not a result of fertiliser, rather, it likely represents a response to dietary preferences [55].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Small-scale piggeries and vegetable cropping also occur in the catchment of the farms, and urban activities in the nearby town of Kainantu, may also be sources of nutrients; however, their contribution to the nutrient budgets of the farms is likely to be negligible. Despite the use of chicken manure, a previous study has shown that this type of organic fertiliser does not influence the growth and δ 15 N of GIFT [11]. This indicates that the enrichment of δ 15 N in vegetable-fed GIFT in our study is not a result of fertiliser, rather, it likely represents a response to dietary preferences [55].…”
Section: Discussionmentioning
confidence: 48%
“…As for many farmed species, commercial fish feed pellets are widely considered the best option to increase GIFT farm productivity; however, only 10% of the small-scale fish farmers in PNG use commercial fish feed [ 10 ]. Whilst the nutritional needs of farmed tilapia can be met through a variety of natural food sources [ 11 ], a poor diet can negatively impact their growth and overall health [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, studies in fish nutrition have incorporated the stable isotope analysis tool to assess the quantity and quality of food assimilation by fish in farming environments (Abimorad et al, 2017; Asano et al, 2010; Filbrun et al, 2013; Jomori et al, 2008; Narimbi et al, 2018), since the isotopic compositions of animal tissues resemble their diets (Ducatti, 2007; Franco et al, 2014). Given the similarity of the isotopic signal between fish fed with live and frozen zooplankton at the end of feed training, we can conclude it that there was a similar amount of these foods consumed by the fish, without preference for the way the zooplankton was supplied.…”
Section: Discussionmentioning
confidence: 99%
“…The study results pointed to a more sustainable feed management in the farming of Nile tilapia in net cages. In a study on the same tilapia species (GIFT strain), but grown in earthen ponds, Narimbi et al 86 applied carbon and nitrogen SIA to determine the role of supplementary feed and natural food sources. Isotopic values of tilapia muscle and potential food sources indicated that compound feed contributed from 7% to 33%, depending on feeding frequency, to the growth of fish.…”
Section: Natural Biota Versus Formulated Feedsmentioning
confidence: 99%